Indicadores productivos y reproductivos de la ganadería en la parroquia Guayzimi, cantón Nangaritza de la provincia de Zamora Chinchipe, Ecuador - Coronel Carpio, María Fernanda (2023)
Cattle raising is one of the most distributed and important activities for its economic contribution, however, the lack of technification such as the use of registers has caused a setback in its growth, causing low productions and therefore low economic gains. Therefore, we propose to evaluate the productive and reproductive indicators of livestock in the Guayzimi parish, Nangaritza canton of the province of Zamora Chinchipe. A survey was applied, including questions related to social, productive and reproductive aspects, directly to 35 cattle ranchers in the study area between November and December 2022. The information obtained was organized in a data matrix and then a principal component analysis was applied, some dispersion and position statistics were obtained and a multiple correlation matrix was made. The results obtained allowed the identification of three main components related to social (79.19%), productive (14.22%) and reproductive (6.59%) aspects, which together were able to explain 100% of the variance obtained in the study. Based on the data obtained, it was possible to determine the degree of importance of the indicators studied, where the social aspect is one of the links that most affects cattle raising in the parish. The productive and reproductive indicators studied presented a high degree of correlation, showing an interdependence between them. In addition, high levels were observed in the coefficients of variation of all the variables studied, related to multiple factors that denote the need for further research to identify them in a timely manner. Key words: productive indicators, reproductive indicators, livestock, Guayzimi.